Problemy identyfikacji narodowo-politycznej w RFN - Perlak, Bernard (Wydział Prawa i Administracji UAM, 1982)
A vital role in the study of problems of the national and political identification is played by a category of historical consciousness. There are many kinds of the historical consciousness in a society. The historical consciousness of a nation is in a way its highest form. The consciousnes advised by a ruling class aims to strengthen its position. Yet it can follow neither a tradition nor the consciousness of the society. From the point of view of the national and State identification, the FRG citizens have difficulties with their identification with the German history. They reject totalitarian elements of it, or actually, they claim they do so, without discarding their tradition which was mainly antidemocratic. The non-Marxist ideologues and politicians in the West Germany are worrying about the decline of the „all-German" identification in the society. They strive to maintain it, basing it on elements of the tradition and attempting to reconstruct it in the spirit of the burgeois — democracy. It would be fallacious to claim that the national and political history of Germany has been fully accepted. At the same time the system of parliamentary burgeois democracy is thought to be an antithesis of the national socialism and the "totalitarianism" of the socialist states. Loss of historical consciousness in the West German society can be considered as a favourable phenomenon in the aspect of political and ideological interests of the proprietary classes and not favourable from the point of view of the same class aspiring to regain power upon the whole German nation. Problems of crisis in the German historical consciousness can be examined from the angle of the society's search of its own place between the past and the present time while at the same time feelings of separateness of the society ("we, citizens of the FRG" vs. "other Germans") are getting deeper. One can venture a statement that the "new" historical consciousness is mostly to serve the class and national interests of the FRG. Still, the West German scholars agree that only a democratic re-evaluation of the German historical tradition can create grounds for German self-recovery in the new socio-political and ideological situation. That would have to amount to the acceptance of changes in the German historical consciousness which have occured in the Western Germany after the World War II. There is a discussion going on in the FRG on the "German identity" crisis and on the national and State self understanding. It is stimulated by the opinion that the "official line of interpretation" of history, mainly in the teaching process, can effect shaping of the historical consciousness mainly in its state and national spheres. Hence, the identification with the FDR and its system can be intensified as well as the German sentiments- "animated" through a "revival" in the teaching of history. It can signify a partial revision of the existing tradition without giving up the fundamental goal i.e. unification of Germany. The historical consciousness in the state and national spheres has to be developed in accordance with those ideals. Many German scholars can notice that insufficient historical knowledge can result in a political indifference, which in turn under the favourable circumstances can be transformed into the emotional nationalism. Being a tool of integration of the society based on certain patterns and values formed on the grounds of certain historical tradition, the national and political consciousness adopted different forms in Western and in Eastern Germany, which are subject to various class and ideological needs. The national tradition understood as the all-German integrating element and the "new" historical consciousness modelled on it along the principles of the Western democracy could develop only in the Federal Republic of Germany. And yet, there have been some attempts to impose it upon the society of the socialist German state. More and more frequent calls in the FRG to "revive" the German national consciousness can result in its rebirth in the old nationalistic form. Some of the West German scholars can perceive that danger, but some of them can not. The latter claim that the democratic ideals have permanently entered the consciousness of the West German society. Therefore, the old anti-democratic German nationalism has neither the reason nor the posibility to exist. The history developed in the spirit of democracy can become a foundation of political integration in the two meanings of that term: as a factor maintaining the feelings and sentiments of German community and as an element of identification of the FRG citizens with their own State.
Problems of the National and Political Identification and the National Historical Consciousness in the Federal Republic of Germany